2023
DOI: 10.1111/1755-0998.13801
|View full text |Cite
|
Sign up to set email alerts
|

A second unveiling: Haplotig masking of the eastern oyster genome improves population‐level inference

Abstract: Genome assembly can be challenging for species that are characterized by high amounts of polymorphism, heterozygosity, and large effective population sizes. High levels of heterozygosity can result in genome mis‐assemblies and a larger than expected genome size due to the haplotig versions of a single locus being assembled as separate loci. Here, we describe the first chromosome‐level genome for the eastern oyster, Crassostrea virginica. Publicly released and annotated in 2017, the assembly has a scaffold N50 … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 77 publications
0
6
0
Order By: Relevance
“…By conditioning adult eastern oysters in a controlled laboratory environment and comparing female and male global expression profiles in reproductively ripe gonad and mantle tissues, we confirmed that many conserved sex differentiation genes are present and predictably expressed in eastern oysters. Deep sequencing of individual transcriptomes and subsequent mapping to the highly contiguous, chromosome-level eastern oyster genome assembly (Puritz et al, 2023) also provided opportunity for more in-depth exploration of sexspecific processes in gonad and mantle tissues. Many transcripts associated with flagellar formation, spermiogenesis, and degradation of damaged sperm were identified in male gonad, whereas those involved in cell cycle regulation were observed in female gonad.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…By conditioning adult eastern oysters in a controlled laboratory environment and comparing female and male global expression profiles in reproductively ripe gonad and mantle tissues, we confirmed that many conserved sex differentiation genes are present and predictably expressed in eastern oysters. Deep sequencing of individual transcriptomes and subsequent mapping to the highly contiguous, chromosome-level eastern oyster genome assembly (Puritz et al, 2023) also provided opportunity for more in-depth exploration of sexspecific processes in gonad and mantle tissues. Many transcripts associated with flagellar formation, spermiogenesis, and degradation of damaged sperm were identified in male gonad, whereas those involved in cell cycle regulation were observed in female gonad.…”
Section: Discussionmentioning
confidence: 99%
“…Trimmed reads were mapped to a haplotig masked version (Puritz et al, 2023) of the Crassostrea virginica genome v3.0 (NCBI; GCA_002022765.4) using CLC Genomic Workbench's RNA-Seq Analysis tool. To account for high polymorphism in oysters (L. Zhang, Li, et al, 2014), the length fraction setting was reduced to 0.6 as in Proestou and Sullivan (2020), while all other settings were kept at default.…”
Section: Rna Sequencing and Mappingmentioning
confidence: 99%
See 1 more Smart Citation
“…Mitochondrial SNPs on the array were excluded. SNPs located in putative inversions (Puritz et al., 2022 , 2023 ) were excluded to prevent artifacts in population structure patterns from long‐range linkage disequilibrium. Additional filtering steps were applied using VCFtools (Danecek et al., 2011 ): excluded SNPs with minor allele frequency < 0.05 across 18 wild and domestic populations combined; individuals were removed if they had >10% missing data; SNPs with a call rate less than 95% in any single population were excluded.…”
Section: Methodsmentioning
confidence: 99%
“…Then the phylogenetic tree was estimated using RaxML v.8.2.12 (Stamatakis, 2014). Finally, the divergence time was estimated using MCMCTree from PAML v.4.9 (Yang, 2007) (Puritz et al, 2023). The calibration divergence of C. virginica and C. angulata was estimated at 73 Ma (Plazzi & Passamonti, 2010;Ren et al, 2010).…”
Section: Phylogenetic Analysis Of Southern-northern Oyster Speciesmentioning
confidence: 99%